Technical guidance for preparing financial reports at small and medium enterprises (SMEs) “Bluesummer” - Farida Farida; Akhria Kukuh Widyastuti; Arda Laksmana Anugraha; Heni Sofi; Nandila Feby Izami; Nurul Wahid (Community Empowerment, 2022)
Financial reports are prepared to give data regarding MSMEs' performance and are helpful for business decision-making. In general, MSME actors simply keep simple documentation of their income and expenses. Some even fail to include rent as an operational expense, which gives the impression that the company is making a lot of money despite the improperly documented expenses. As a result, the report does not accurately reflect the company's current financial situation. The purpose of this community service is to provide socialization, training and information on the preparation and financial reporting of MSMEs. This activity is carried out by giving instruction on how to create financial reports using the MSME application and the Excel program. The results achieved from this program are increased knowledge and skills of partners in preparing financial reports, so that financial performance can be measured.